2022
DOI: 10.21037/tgh.2020.02.11
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy after Roux-en-Y Gastric Bypass: a novel reconstruction technique

Abstract: BackgroundThe obesity epidemic continues to increase around the world with its attendant complications of metabolic syndrome and increased risk of malignancies (1), including pancreatic malignancy (2,3). The Roux-en-Y gastric bypass (RYGB) effectively treats obesity and its associated morbidities including metabolic syndrome (4). RYGB creates a gastric pouch with alimentary limb, as well as a biliopancreatic (BP) limb that joins the alimentary limb to form a common channel. Thus, it has both restrictive and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This study was based on 96 patients under 55 different surgeons in 28 centres globally. 4,6,7 Multiple potential options for PD in patients with a previous RYGB have been described in overseas case reports, with the major surgical decisions being the degree of resection/preservation of both the gastric remnant and the biliopancreatic limb. 4 The gross advantages/disadvantages have been described by Mak et…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was based on 96 patients under 55 different surgeons in 28 centres globally. 4,6,7 Multiple potential options for PD in patients with a previous RYGB have been described in overseas case reports, with the major surgical decisions being the degree of resection/preservation of both the gastric remnant and the biliopancreatic limb. 4 The gross advantages/disadvantages have been described by Mak et…”
Section: Discussionmentioning
confidence: 99%
“…Surgical decision making should be tailored to individual patients' anatomy and their associated pathology. 4,6…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence cholangiocarcinoma post bariatric surgery appeared low, the three reported cases of cholangiocarcinoma were diagnosed at an advanced stage (Beghdadi, 2020). Cases by Tumour Type 3,[24][25][26][27][28]31 of the 24 cases. These were distributed as follow; Pain (4), Pain and Jaundice (3), Jaundice and Weight loss (1), Jaundice (1), and Incidental finding (4).…”
Section: Cholangiocarcinomamentioning
confidence: 97%
“…The review found 11 authors that reported pancreatic and cholangiocarcinoma with total 27 reported cases 3,19,[22][23][24][25][26][27][28][29][30][31] .…”
Section: Reported Cases Post Bariatric Surgerymentioning
confidence: 99%
See 1 more Smart Citation